Sticky: The Vazaleen Posters - Clintberg, Mark (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2019)
Vazaleen was a monthly serial queer party in Toronto founded by artist and promoter Will Munro (1975-2010) in 2000. Munro commissioned Toronto-based artist Michael Comeau (1975-) to create many silkscreen poster advertisements for these parties. His designs include an array of typographic treatments, references to popular culture and queer icons, and vibrant colour schemes. This article discusses these posters in relationship to Michel Foucault’s theory of the heterotopia, Roland Barthes’ semiotic analysis of advertising, and Eve Kosofsky Sedgwick’s writing on camp.